2005
DOI: 10.1007/s11292-005-8126-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of face-to-face restorative justice on victims of crime in four randomized, controlled trials

Abstract: The growing use of restorative justice provides a major opportunity for experimental criminology and evidence-based policy. Face-to-face meetings led by police officers between crime victims and their offenders are predicted to reduce the harm to victims caused by the crime. This prediction is derived not only from the social movement for restorative justice, but also from psychological and sociological theories. Four randomized, controlled trials of this hypothesis in London and Canberra, with point estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(93 citation statements)
references
References 13 publications
4
86
0
3
Order By: Relevance
“…Although our findings are compatible with others showing high apology acceptance rates in the RJ context (Shapland et al, 2006;Sherman et al, 2005), they are also somewhat surprising given the long history of conflict in some of the cases. Bennett and Dewberry (1994) have shown that explicit rejections of apologies are rare, and rather recipients show offense, anger or disapproval.…”
Section: Acceptance Of Apologysupporting
confidence: 91%
“…Although our findings are compatible with others showing high apology acceptance rates in the RJ context (Shapland et al, 2006;Sherman et al, 2005), they are also somewhat surprising given the long history of conflict in some of the cases. Bennett and Dewberry (1994) have shown that explicit rejections of apologies are rare, and rather recipients show offense, anger or disapproval.…”
Section: Acceptance Of Apologysupporting
confidence: 91%
“…(see Strang 2002;Strang et al 2006Strang et al , 2013Sherman et al 2005) Because frequency of criminal convictions (or arrests) is a crude indicator of the amount of harm caused by crime, the review also sought information indicating the seriousness or cost of crime as a measure of impact on repeat offending.…”
Section: Introductionmentioning
confidence: 99%
“…Higher-quality evaluations, as indicated by internal validity, provide more confidence in observed effects, and randomized experiments have the highest internal validity (Farrington andWelsh 2005, 2006;Shadish et al 2002). The second issue was that criminal justice, with few exceptions (e.g., Braga 2005;Sherman et al 2005), does not have the luxury (unlike medicine) to base policies and practices solely on evidence from randomized experiments. Instead, it must consider a wider range of evaluation designs (Mears 2007(Mears , 2010.…”
mentioning
confidence: 99%